EXPERIMENTAL SKILLS IN THE TEACHING-LEARNING PROCESS OF CHEMISTRY IN HIGH SCHOOL EDUCATION: A PROPOSAL FOR EXPERIMENTAL TASKS - Sánchez Fernández , Gerson Alejandro; Álvarez Vega , Betsy; de Villa Amil Sellez, Yisel Pérez (Revista Minerva, 2023)
The objective of this article is to define the experimental skills to be developed from the teaching-learning process of Chemistry in upper secondary education, specifically in 1st year students of the basic secondary teacher specialty of the Chemistry specialty. The analytical-synthetic method, document analysis, observation, survey and interview were used to diagnose and characterize the development of experimental skills in students. A proposal of experimental tasks is provided for the development of experimental skills from the experimental activities of unit 2 "Water and its solutions", in addition the results obtained in the validation of the proposal are explained, using the assessment by specialist criteria. and the application in educational practice.
Keywords: learning; teaching; experiment; experimental skills; experimental tasks